ULTRASOUND GUIDED FINE NEEDLE ASPIRATION CYTOLOGY VERSUS CORE BIOPSY IN THE PREOPERATIVE ASSESSMENT OF NON-PALPABLE BREAST LESIONS - Ahmed, Muhammad Ejaz; Ahmad, Iftikhar; Akhtar, Saleem (Journal of Ayub Medical College Abbottabad, 2010)
Background: Breast screening is a method of detecting breast cancer at a very early stage. Most of the lesions detected by screening are not malignant. Objective of this study was to compare ultrasound guided fine needle aspiration cytology and core biopsy in the preoperative assessment of non-palpable breast lesions. Methods: The study was conducted prospectively at Department of Radiology, Shaukat Khanum Memorial Cancer Hospital and Research Centre, Pakistan from March 2004 to February 2005. All the patients underwent fine needle aspiration cytology and core biopsy. Later on, all of them had excision biopsy/ mastectomy. Prospectively 80 patients were studied; information was collected on a specifically designed form according to inclusion criteria. The patient age, sex, medical record number and side of lesion were recorded. Clinical history of duration of lump was also taken. Informed consent was obtained. Results: The age of patients were ranges from 20-71 years, with mean of 44.31±11.002 and the maximum number of patients 28 (35.3%) was between the ages 50-59 years. The sensitivity of FNAC was 92.85%, while the specificity of was 90% and the accuracy rate was 92.1%. The sensitivity of core biopsy was 94.64%, specificity 91.30% and accuracy rate was 94.87%. Conclusion: Fine Needle Aspiration has been found to be an extremely useful method for the diagnosis of lumps of breast. The accuracy and the sensitivity of diagnosis on fine needle aspiration cytology were high. Keywords: fine needle biopsy, core biopsy, ultrasound guided, non-palpable breast cancer, breast lesion